Relación entre padres - escuela a través de la utilización del facebook como medio de comunicación - Gamarra T., Christiam (2013)
Communication between home and school is vital to maintain a good relation ship and technology has evolved so that you have provided various tools we can use to improve important aspects such as the one mentioned. Initially a short questionnaire was applied in order to identify the group as potentially able to implement the project as it was necessary to check if the group was family to evaluate the use of Facebook as a means of communication. Initially we applied the scale of parent-school diagnosis, the same scale was applied at the end of the time scheduled for the development of research, where it has been observed that the results between the two times differ significantly, whichwe can say that parent school communication is enhanced by the use of Facebook and this in turn leads to better diagnosis of the family-school relation ship.